Children’s listening-participation in Childhood Education (Research, Society and Development, 2020)
This study aims to analyse the means/ways of communicating with children in Early Childhood Education, identifying their participation-listening relationship in the educational routine and how their cultural productions have repercussions on the teacher's pedagogical action in Physical Education spaces. For that, it carries out an ethnography with children, based on the theoretical references of the Sociology of Childhood. As a result, in the analysis process, data from participant observation, recorded through narratives, utterances, drawings, photos, videos and field diaries, showed the conversation wheels, the school's educational project, interactivity through games and games and drawing as potential resources for the identification of peer cultures and dialogical interaction with children in Early Childhood Education. It is inferred that the child participation-listening process requires considering children as subjects and not objects of knowledge production, as well as understanding them in their desires and ways of being, reinforcing the importance of adopting measures of a pedagogical, political nature and administrative to materialize an educational process based on children's rights.